Search for α condensed states in ^13C using α inelastic scattering. (11th August 2021) - Inaba, K; Sasamoto, Y; Kawabata, T; Fujiwara, M; Funaki, Y; Hatanaka, K; Itoh, K; Itoh, M; Kawase, K; Matsubara, H; Maeda, Y; Suda, K; et al.
Abstract: We searched for the α condensed state in ^13 C by measuring the α inelastic scattering at E_α = 388 MeV at forward angles including 0^° . We performed a distorted-wave Born approximation calculation with the single-folding potential and multipole decomposition analysis to determine the isoscalar transition strengths in ^13 C. We found a bump structure around E_x = 12.5 MeV due to the isoscalar monopole (IS0 ) transition. A peak-fit analysis suggested that this bump consisted of several 1/2^- states. We propose that this bump is due to the mirror state of the 13.5 MeV state in ^13 N, which dominantly decays to the α condensed state in ^12 C. It was speculated that the 1/2^- states around E_x = 12.5 MeV were candidates for the α condensed state, but the 3α + n orthogonality condition model suggests that the α condensed state is unlikely to emerge as the negative parity states. We also found two 1/2^+ or 3/2^+ states at E_x = 14.5 and 16.1 MeV excited with the isoscalar dipole (IS1 ) strengths. We suggest that the 16.1 MeV state is a possible candidate for the α condensed state predicted by the cluster model calculations on the basis of the good correspondence between the experimental and calculated level structures. However, the theoretical IS1 transition strength for this state is significantly smaller than the measured value. Further experimental information is strongly desired to establish the α condensed state in ^13 C.